2013
DOI: 10.1007/s00170-013-5292-3
|View full text |Cite
|
Sign up to set email alerts
|

Laser surface hardening of 42CrMo cast steel for obtaining a wide and uniform hardened layer by shaped beams

Abstract: For laser surface hardening (LSH) of large-sized workpieces, a wide and uniform hardened layer of a single track is pursued. In this study, two kinds of shaped laser beams were used in LSH of 42CrMo cast steel to obtain the required hardened layer. One is a stripy spot with uniform-intensity array spots and the other a stripy spot with intensity blowup in the edge of the whole array spots. As a comparison, a Gaussian laser beam was also adopted. A three-dimensional finite element model was used to simulate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…The laser surface processing [7,8] resulting in melting [9], transformation hardening [10] or severe plastic deformation [11] of metallic surfaces, the surface treatments using electron beam [12], and plasma arc [13], as well as surface mechanical attrition treatment [6], deep ball-burnishing [14], ultrasonic impact treatment (UIT) [15][16][17], and ultrasonic nanocrystal surface modification [18] are promising cost-effective methods for surface hardening, surface polishing and formation of regular microrelief. As compared to the traditional energy sources for thermal hardening laser surface hardening (LSH) used the focused laser beam has the advantage over the other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The laser surface processing [7,8] resulting in melting [9], transformation hardening [10] or severe plastic deformation [11] of metallic surfaces, the surface treatments using electron beam [12], and plasma arc [13], as well as surface mechanical attrition treatment [6], deep ball-burnishing [14], ultrasonic impact treatment (UIT) [15][16][17], and ultrasonic nanocrystal surface modification [18] are promising cost-effective methods for surface hardening, surface polishing and formation of regular microrelief. As compared to the traditional energy sources for thermal hardening laser surface hardening (LSH) used the focused laser beam has the advantage over the other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In article [4] was found that the combination of radial and circular scan schemes works better for achieving higher bending angle of the obtained surface. Due to the high peak temperature and heating rate caused by the latter shaped beam, a higher value of micro hardness in the transformation hardened zone was found in article [5]. In work [6], two different irradiating schemes were used and compared for flame forming of a bowl-shaped surface and it was proved that the obtained bowl-shaped surface with spiral irradiating scheme has larger curvatures and symmetry and lower residual stresses in comparison with the obtained bowl-shaped surface with combined irradiating scheme.…”
Section: Introductionmentioning
confidence: 97%
“…Laser surface hardening is a heat treatment process that uses a high energy density laser in a localized heating zone [1,2]. Applying this process on steel parts and coupling it with a fast quenching technique, called martensitic quenching, allow improving fatigue life and limit the distortion of steel parts [3][4][5].…”
Section: Introductionmentioning
confidence: 99%